Continuous Inotrope Therapy in Hospice Care: A Case Series. (July 2019) - Patel, Krishna; D'Souza, Andre; Groninger, Hunter
Background: Continuous cardiac inotropes are increasingly utilized for symptom management in advanced heart failure (AHF). Among patients who are not eligible for cardiac transplant or mechanical circulatory support, many are hospice eligible at the time of inotrope initiation. Nevertheless, given relative infrequent use as well as cost issues, acceptability and management of inotropes in the hospice setting are likely widely variable between hospice agencies. Objective: To describe hospice care experiences for patients with AHF receiving continuous inotrope therapies and weaning inotropes at the end of life. Design: Single-institution retrospective chart review of patients with AHF receiving continuous inotropes who were discharged from the hospital to hospice care between February 2015 and October 2016 and survey of hospice medical directors providing direct care of these patients. Results: Eighteen patients with AHF receiving continuous inotropes were discharged to 6 hospice agencies. Twelve patients were weaned from inotropes prior to death. Among cases where the inotrope was weaned, patients lived several days to more than 2 weeks. All hospice medical directors surveyed would accept patients on inotropes again. Most believed that providing continuous inotrope therapy for patients with AHF is compatible with the philosophy of hospice care. Conclusion: Cardiac inotropes can align with both the goals of care for the patient with AHF and the philosophy of hospice care. Patients with AHF admitted to hospice care on continuous inotropes may live days to weeks, whether or not inotropes are discontinued.